Low-Temperature H2S Detection with Hierarchical Cr-Doped WO3 Microspheres - Wang, Yanrong (2017)
Hierarchical Cr-doped WO3 microspheres have been successfully synthesized for efficient sensing of H2S gas at low temperatures. The hierarchical structures provide an effective gas diffusion path via well-aligned micro-, meso-, and macroporous architectures, resulting in significant enhancement in sensing response to H2S. The temperature and gas concentration dependence on the sensing properties elucidate that Cr dopants remarkably improve the response and lower the sensor’ operating temperature down to 80 °C. Under 0.1 vol % H2S, the response of Cr-doped WO3 sensor is 6 times larger than pristine WO3 sensor at 80 °C. We suggest the increasing number of oxygen vacancies created by Cr dopants to be the underlying reason for enhancement of charge carrier density and accelerated reactions with H2S.